2016
DOI: 10.3390/polym8040145
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Spherical Polyelectrolyte Brushes by Layer-by-Layer Self-Assembly as Observed by Small Angle X-ray Scattering

Abstract: Abstract:Multilayer modified spherical polyelectrolyte brushes were prepared through alternate deposition of positively charged poly(allylamine hydrochloride) (PAH) and negatively charged poly-L-aspartic acid (PAsp) onto negatively charged spherical poly(acrylic acid) (PAA) brushes (SPBs) on a poly(styrene) core. The charge reversal determined by the zeta potential indicated the success of layer-by-layer (LBL) deposition. The change of the structure during the construction of multilayer modified SPBs was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
20
2
Order By: Relevance
“…The data analysis in this work was done as described in the literatures . The scattering intensity, I ( q ), can be expressed as a function of the scattering vector q which is determined according to the following equation: q=()4πλ0.25emsin()θ2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data analysis in this work was done as described in the literatures . The scattering intensity, I ( q ), can be expressed as a function of the scattering vector q which is determined according to the following equation: q=()4πλ0.25emsin()θ2 …”
Section: Methodsmentioning
confidence: 99%
“…This part dominates the scattering intensity at small scattering angles. For a spherical symmetric particle, this term is equal to the square of the scattering amplitude B ( q ), which could be described as shown below: B()q=4italicπb0R[]ρe()rρmer2sinitalicqrqritalicdr where b is the Thomson scattering length and equal to 0.282 × 10 −14 m. R is the radius of the spherical particle, and (ρe()rρme), that is, Δρ e ( r ), denotes the difference between the radial electron density of the particle ρ e ( r ) and the electron density of solvent ρme. Hence, it is obvious that the higher the contrast of electron density between particle and solvent is, the stronger the scattering signal will be.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, small-angle X-ray scattering (SAXS) of hollow capsules could give a detailed illustration of the inner structure and their size distribution in in situ measurements. SAXS investigations of PAH and poly-ʟaspartic acid multilayers deposited on poly(acrylic acid) (PAA) brush modified PS templates indicated that some PAH chains penetrated into the PAA brush [37]. Notably, SAXS proved to be a powerful tool to gain more information about the inner structure of such systems.…”
Section: Core Templatesmentioning
confidence: 99%
“…More detailed tting process can be found in our previous publications. [41][42][43] Results and discussion…”
Section: Characterizationmentioning
confidence: 99%